Vocational Training of Unemployed Workers in Belgium - Bart Leo Wim Cockx (Institute for the Study of Labor (IZA), 2003)
In this paper we estimate, for the 1989-93 period in Belgium, the effect of vocational classroom training on the rate of transition from unemployment. We propose a ?control function? estimator accounting for variable treatment effects. In the absence of interaction effects between explanatory variables this estimator identifies treatment effects free from selection bias. A natural experiment induces exogenous sub-regional variation in the training supply. This provides over-identifying restrictions that cannot be rejected. During participation, the transition rate decreases by 23% to 30%. Afterwards it increases by 47% to 73%. Making training available for a broader population would, however, reduce the effectiveness of the programme.
Keywords: J68; J64; C41; J24; 330; vocational training; evaluation; transition models; job-search; Berufsbildung; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Berufliche Integration; Schätzung; Belgien